Isolation of high lipids content microalgae from Wonorejo rivers, Surabaya, Indonesia and its identification using rbcL marker gene - TRIONO BAGUS SAPUTRO; KRISTANTI INDAH PURWANI; DINI ERMAVITALINI; ARIF FUAD SAIFULLAH (Society for Indonesian Biodiversity, 2019)
Abstract. Saputro TB, Purwani KI, Ermavitalini D, Saifullah AF. 2019. Isolation of high lipids content microalgae from Wonorejo river, Surabaya, Indonesia and its identification using rbcL marker gene. Biodiversitas 20: 1380-1388. Microalgae are unicellular organism which possesses various biologically active metabolites that used in food, cosmetic, pharmaceutical, nutraceutical, and bioenergy industries. One of the most important active metabolites found in microalgae is lipid which can be converted into biodiesel. The higher amount of lipid produced will increases the amount of biodiesel that can be obtained. Although, the production of active metabolites in microalgae has rather fluctuated as it is difficult to obtain the pure cultures of microalgae since it has a cryptic phenomenon. This problem can be solved through identification technique using molecular markers or DNA Barcoding. This research used rbcL gene as the molecular marker in species identification. rbcL gene encode ribulose-1,5-bisphosphate carboxylase (RubisCo) in chloroplast genome. Furthermore, microalgae were isolated from 3 different stations of Wonorejo river estuary, Surabaya, East Java, Indonesia. The isolated microalgae were then identified based on Freshwater algae: identification and use as bioindicators book. Eight isolates were successfully identified as Mycrocystis sp., Nostoc sp., Chlorella sp., Tabellaria, Synedra, Nitzschia, Navicula, and Closteriopsis. Out of eight, only 3 species that has a good potential to be developed as biodiesel sources i.e Chlorella sp., Synedra sp., and Navicula sp. that produce 21,20%, 20,30%, 27,20% of total lipids over their biomass. The genomic DNA from those three candidates were then isolated and used as a template to amplify rbcL gene. The obtained fragment of rbcL gene was sequenced and then submitted to the Basic Local Alignment Search Tool (BLAST). The result of BLAST used for alignment and phylogenetic tree construction. The result from BLAST shows the same results as the genus observed by microscopy observation. Overall, this research provides information about the genetic variety of microalgae in Wonorejo which has high potential to be further developed as biodiesel.